Incidence and related factors of hypoxia associated with elderly femoral neck fractures in the emergency department setting. Issue 1 (20th December 2020) - Hongo, Takashi; Naito, Hiromichi; Fujiwara, Toshifumi; Inaba, Mototaka; Fujisaki, Noritomo; Nakao, Atsunori
Abstract : Aim: Femoral neck fractures in elderly patients needing oxygen therapy are often encountered in the emergency department. This single‐center, retrospective, observational study aimed to examine the frequency, cause, and factors related to hypoxia in elderly patients with femoral neck fractures. Methods: We analyzed data from 241 patients admitted to Okayama Saiseikai General Hospital (Okayama, Japan) from April 2016 to March 2019. Hypoxia was defined as PaO2 / FiO2 ratio under 300. The independent factors for hypoxia were determined by multiple logistic regression analysis. Results: There were 194 patients who met the study inclusion criteria, 148 in the non‐hypoxia group and 46 in the hypoxia group. The hypoxia group included patients with pneumonia ( n = 3), chronic obstructive pulmonary disease ( n = 2), pulmonary edema ( n = 1), and pulmonary embolization ( n = 1). The cause of hypoxia was undetermined in 39 cases. However, occult fat embolism syndrome was suspected in 29 of these 39 cases based on Gurd and Wilson criteria after considering clinical examination results. Barthel indexes were significantly lower in the hypoxia group on discharge. Age (adjusted odds ratio [OR] 1.07; 95% confidence interval [CI], 1.00–1.14; P = 0.038), D‐dimer (adjusted OR 1.02; 95% CI, 1.00–1.03; P = 0.005), and transtricuspid pressure gradient (adjusted OR 1.03; 95% CI, 1.00–1.07; P = 0.015) were independently associated with the hypoxia. Conclusion: We found that hypoxia, including undetermined hypoxia, was commonly encountered in the emergency department. Hypoxia in elderly patients with femoral neck fractures was associated with age, D‐dimer, and transtricuspid pressure gradient and needs further investigation. Abstract : In the multivariable analysis, age (adjusted odds ratio [OR] 1.07; 95% confidence interval [CI], 1.00–1.14; P = 0.038) D‐dimer (adjusted OR 1.02; 95% CI, 1.00–1.03; P = 0.005), and transtricuspid pressure gradient (adjusted OR 1.03; 95% CI, 1.00–1.07; P = 0.015) were independently associated with hypoxia in patients with femoral neck fractures.